English Needs Analysis of Electrical Engineering Students, Graduates, and Companies: A Step toward Employability - Abbas Ali Rezaee; Samira Kazempourian (Journal of Language Horizons, 2017)
English for Specific Purposes (ESP) program constitutes a significant part of university curricula in most countries. Iran is no exception. To aid students to succeed in their academic studies and later in their future job, ESP courses should be based on their academic and professional language needs. Therefore, this study intended to investigate the English language needs of Electrical Engineering (EE) students and graduates from their own perspectives, along with the English language expectations of Electrical companies from the employers’ point of view. To fulfill this end, a questionnaire was administered to three different groups of stakeholders, including 97 EE students, 62 EE graduates, and 39 EE employers from 15 well-reputed Electrical companies in Iran. Moreover, semi-structured interviews and observations were conducted. Having collected the required data, the researchers did content analysis and ran independent sample t-test for doing the statistical analyses. The results indicated that different aspects of ‘reading’, ‘speaking’, ‘listening’, ‘writing’, and ‘study skills’ with different degrees of emphasis were important for each group of stakeholders. Moreover, the findings revealed that EE companies expected their prospective EE graduates to be more proficient in ‘reading’, ‘study skills’, and ‘speaking’. The findings have some implications for ESP curriculum developers so that they would consider the English requirements of relevant companies. Keywords: ESP, Employability, Electrical Engineering, Needs Analysis.